An improved TK-NOG mouse as a novel platform for humanized liver that overcomes limitations in both male and female animals - Uehara, Shotaro; Higuchi, Yuichiro; Yoneda, Nao; Kawai, Kenji; Yamamoto, Masafumi; Kamimura, Hidetaka; Iida, Yuichi; Oshimura, Mitsuo; Kazuki, Yasuhiro; Yamazaki, Hiroshi; Hikita, Hayato; Takehara, Tetsuo; et al. (Drug metabolism and pharmacokinetics, 2022)
We developed a novel immunodeficient NOG mouse expressing HSVtk mutant clone 30 cDNA under the control of mouse transthyretin gene enhancer/promoter (NOG-TKm30) to acquire fertility in males and high inducibility of liver injury in females. Maximum human albumin levels (approx. 15 mg/mL plasma) in both male and female NOG-TKm30 mice engrafted with human hepatocytes (humanized liver mice) were observed 8–12 weeks after transplantation. Immunohistochemical analyses revealed abundant expression of major human cytochrome P450 (CYP) enzymes (CYP1A2, CYP2C9, CYP2D6, CYP2E1, and CYP3A4) in reconstituted liver with original zonal distribution. In vivo drug–drug interactions were observed in humanized liver mice as decreased area under the curve of midazolam (CYP3A4/5 substrate) and omeprazole (CYP3A4/5 and CYP2C19 substrate) after oral administration of rifampicin. Furthermore, we developed a pregnant model for evaluating prenatal exposure to drugs. The detection of thalidomide metabolites in the fetuses of pregnant humanized liver mice indicates that the novel TK model can be used for developmental toxicity studies requiring the assessment of human drug metabolism. These results suggest that the limitations of traditional TK-NOG mice can be addressed using NOG-TKm30 mice, which constitute a novel platform for humanized liver for both in vivo and in vitro studies.